Pendidikan dalam perspektif islam dan peranannya dalam membina kepribadian islami - Herwati, Herwati (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2024)
This study aims to explore education in Islamic perspective and its role in fostering Islamic personality. Using a qualitative approach, this research involved in-depth interviews, participatory observation, and document analysis in several Islamic educational institutions in Indonesia. The research subjects included educators, scholars, students and parents involved in Islamic education. The results showed that Islamic education has a holistic approach that includes cognitive, affective and psychomotor aspects. Islamic education emphasizes the importance of developing morals and character in accordance with Islamic values, including honesty, discipline, responsibility and social care. The findings of this study reveal that Islamic education focuses not only on religious knowledge but also on the formation of daily behaviors that reflect noble morals. The educational process involving the integration of Islamic values in the curriculum and interactive and contextual teaching methods proved effective in instilling these values in students. In addition, the active involvement of parents and the community in the educational process is crucial in shaping the Islamic personality of the child. The results also show that Islamic education has a significant role in creating individuals who are not only knowledgeable but also have a strong Islamic personality, able to face modern challenges while adhering to religious principles. Thus, this research confirms the importance of Islamic education in fostering a noble personality and making a positive contribution to society. A holistic and balanced Islamic education is expected to produce a generation that is ready to face the dynamics of life with a solid foundation of Islamic values.